Industrial railroad to digital memory routes: remembering the last railway in Singapore. (September 2014) - Liew, Kai Khiun; Pang, Natalie; Chan, Brenda
The Keretapi Tanah Melayu (KTM) Berhad railway line was a crucial mode of transport for goods and passengers moving between Singapore and its neighbouring country Malaysia. Tanjong Pagar railway station – the terminus of the KTM railway line in Singapore – ceased operation from 1 July 2011, and KTM railway tracks in Singapore were slated for removal, after the relocation of the terminus to a border station between the two countries. This event has led to various initiatives by the state and civil society to remember the KTM railway. This article explores how people utilize Web 2.0 technologies to archive and share railway memories in Singapore. The differences between state-initiated websites and grassroots efforts of remembering the KTM railway bring into question the nature of state–society relations in the practices of memory-making in the digital era. Once reliant on state-run museums, Singaporeans are now remembering the KTM railway tracks through volumes of still and moving images that they have captured themselves, enabled by digital cameras and social media tools. The use of digital media has shaped not only how the railway in Singapore is remembered, but also who participates in remembering.